Assistance in Developing STEM-Based Independent Curriculum Learning Tools Integrated with the Muaro Jambi Temple Archaeological Site for Teachers at SMPN 17 Kota Jambi - Dani, Rahma; M.Salam, M.Salam; Sanusi, Anwar; Hudaya, Padhil; Saputra, Ade Bayu; Lestari, Neneng (Universitas Pahlawan Tuanku Tambusai, 2024)
In the context of the Independent Curriculum (Kurikulum Merdeka), emphasis is placed on integrating elements of local wisdom into the learning process to support the development of student profiles aligned with Pancasila principles. Therefore, teachers are expected to prepare instructional materials that incorporate elements of local heritage in line with the Independent Curriculum. However, field observations, particularly in Kota Jambi, indicate that some schools, such as SMPN 17 Kota Jambi, still rely on teaching materials based on the previous curriculum, which do not incorporate local heritage or STEM aspects related to cultural sites. The purpose of this community service activity is to train teachers at SMPN 17 Kota Jambi to develop Independent Curriculum learning tools that integrate local wisdom and STEM aspects using the Muaro Jambi Temple archaeological site as a contextual learning source. Heyzine was utilized in this program to create interactive digital learning modules, enabling teachers to visually and contextually present the cultural significance of the Muaro Jambi Temple site. The method used in this activity is a workshop comprising three stages: preparation, implementation, and evaluation. This training took place on August 29, 2024, at SMPN 17 Kota Jambi. The results of this training indicate that teachers at SMPN 17 Kota Jambi gained a solid understanding of the concepts, techniques, and use of Heyzine in preparing learning tools in line with the Independent Curriculum, thereby enabling more effective integration of local heritage and STEM aspects associated with the Muaro Jambi Temple into the learning process.